2014
DOI: 10.1016/j.jtemb.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron levels in the human brain: A post-mortem study of anatomical region differences and age-related changes

Abstract: The link between brain iron homeostasis and neurodegenerative disease has been the subject of extensive research. There is increasing evidence of iron accumulation during ageing, and altered iron levels in some specific brain regions in neurodegenerative disease patients have been reported. Using graphite furnace atomic absorption spectrometry after microwave-assisted acid digestion of the samples, iron levels were determined in 14 different areas of the human brain [frontal cortex, superior and middle tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
126
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 38 publications
19
126
0
4
Order By: Relevance
“…10 and Table 2), which are consistent with previous in vivo MRI Li et al, 2014;Poynton et al, 2015;Rodrigue et al, 2013;AcostaCabronero et al 2016) and post-mortem iron analyses (Hallgren and Sourander, 1958;Ramos et al, 2014). Furthermore, the findings presented here also agree with the aforementioned studies in that independent of age, the basal ganglia system, RN and cerebellar DN contain more iron than the thalamus, hippocampus, amygdala, isocortex and WM.…”
Section: Discussionsupporting
confidence: 92%
“…10 and Table 2), which are consistent with previous in vivo MRI Li et al, 2014;Poynton et al, 2015;Rodrigue et al, 2013;AcostaCabronero et al 2016) and post-mortem iron analyses (Hallgren and Sourander, 1958;Ramos et al, 2014). Furthermore, the findings presented here also agree with the aforementioned studies in that independent of age, the basal ganglia system, RN and cerebellar DN contain more iron than the thalamus, hippocampus, amygdala, isocortex and WM.…”
Section: Discussionsupporting
confidence: 92%
“…Non-heme iron can only be studied directly postmortem (Hallgren & Sourander, 1958; Morris, Candy, Oakley, Bloxham, & Edwardson, 1992; Ramos et al, 2014; Ward et al, 2014), while in-vivo magnetic resonance imaging (MRI) can estimate iron deposits based on the interplay between its paramagnetic properties and the proton relaxation resonance behavior of tissue water (Schenck, 2003). Most of the non-heme iron in the brain affecting the MRI signal is believed to be consisting of ferritin and hemosiderin (Schenck, 2003; Schenck & Zimmerman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-menstrual blood loss reduces peripheral iron levels in women and may contribute to sex differences in brain iron accumulation (Tischler et al, 2012; Whitfield et al, 2003). Women had lower levels of brain iron compared to men from midlife to old age according to a recent histologic report (Ramos et al, 2014). Sex steroids, whose levels change post menopause (Al-Azzawi & Palacios, 2009), may also influence sex related variations of brain iron levels (Gu, Xi, Liu, Keep, & Hua, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Increased iron deposition has been found, especially in the hippocampus, in some cases of AD. 17 Post-mortem studies have indicated that the brain stores more iron as it ages and imaging studies by Bartzokis and others have shown increased levels of iron in the hippocampus and basal ganglia of patients with AD, PD and Huntington's disease. 18 The very rapid cognitive decline in our case could be linked with iron deposition.…”
Section: Discussionmentioning
confidence: 99%